ANALISIS KEMANDIRIAN BELAJAR SISWA SELAMA PEMBELAJARAN DARING: (Studi Tentang Model dan Penerapannya di MTs Swasta Zakiyun Najah Sei Rampah) - Yusri, Dairina; Dausat, Jangky; Adnin, Ali Yukla; Sahrul, Sahrul (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2020)
This study aims to analyze: (1) The ability of MTs students. Private Zakiyun Najah Sei Rampah in learning independently during online learning, (2) Model and application of online learning at Zakiyun Najah Private School, (3) constraints on the application of online learning at MTs Zakiyun Najah Sei Rampah. This research uses qualitative research methods, based on descriptive studies. With data collection techniques used include interviews, observation, and documentation. The results of this study indicate that the independent learning of students through online learning is created slowly; this is due to the various limitations possessed by teachers and students. The model and application of online learning is carried out by providing subject matter through assignments given through remote arak with the android application system, WA and video calls. Many obstacles faced by students in implementing online learning include ownership of an android, network limitations, and the inability to buy packages.